Evolution of Anemia Types During Antiretroviral Therapy—Implications for Treatment Outcomes and Quality of Life Among HIV-Infected Adults - Ezeamama, Amara E.; Sikorskii, Alla; Bajwa, Ramanpreet K.; Tuke, Robert; Kyeyune, Rachel B.; Fenton, Jenifer I.; Guwatudde, David; Fawzi, WafaieW. (Nutrients, 2019)
This study examined whether the type of anemia in persons living with HIV/AIDS (PLWHA) changed from the beginning of highly antiretroviral therapy (HAART) and had implications for treatment outcomes and quality of life (QOL). If present, the anemia-type was defined as microcytic, macrocytic or anemia of chronic disease (ACD) at study months 0, 6, 12, and 18. Multinomial logistic regression quantified sociodemographic and HIV-treatment factors associated with incident microcytic anemia or ACD over 18 months. Repeated measures linear regression models estimated the anemia-type associated change in the CD4 cell-count, QOL, body mass index (BMI) and frailty over 18 months. Cox proportional hazard models estimated associations between anemia-type and time to (a) gain at least 100 CD4 cells/L and (b) hospitalization/death. Analyses were implemented in Statistical Analysis Software (v.9.4) from which odds ratios (ORs) mean differences ( ) and corresponding 95% confidence intervals (CI) were estimated. At enrollment, ACD, macrocytic and microcytic anemia was present in 36.8% (n = 147), 11.3% (n = 45) and 9.5% (n = 38), respectively with 42% (n = 170) anemia-free. By the study end, only 23% (n = 115) were without anemia. Among the 251 with anemia at the study end, 53.3% (n = 195) had macrocytic anemia, 12.8% (n = 47) had ACD and 2.5% (n = 9) had microcytic anemia. Incident macrocytic anemia was positively associated with baseline hyperferritinemia (OR = 1.85, 95%CI: 1.03–3.32), inversely associated with wealth (OR = 0.87, 95%CI: 0.67–1.03) and inversely associated with efavirenz-containing HAART (OR = 0.42, 95%CI: 0.21–0.85). ACD incidence decreased by 53% (95%CI: 0.27–0.79) per 100 cells/L increase in baseline CD4-cell count and decreased by 90% (95%CI: 0.01,0.87) among adults treated with nevirapine-containing HAART. ACD was associated with a lower BMI at months 6 ( = 􀀀0.33, 95% CI: 􀀀0.64, 􀀀0.01) and 12 ( = 􀀀0.41, 95%CI: 􀀀0.73, 􀀀0.09), with lower QOL ( = 􀀀3.2, 95%CI: 􀀀5.94, 􀀀0.53) at month 12 and with elevated frailty ( = 1.2; 95%CI: 0.46, 1.86) at month 12. Macrocytic anemia did not predict a post-enrollment change in CD4, BMI or QOL during follow-up. However, the time to gain 100 CD4 cells/L was 43% slower (p < 0.05) and the frailty was higher at month 12 for PLWHA with the baseline or sustained macrocytic vs. no anemia. A substantial decline in ACD and microcytic anemia occurred in tandem with large increase in the macrocytic anemia over 18 months on HAART. Interventions to mitigate all anemia—particularly ACD, is expected to improve the immune recovery rate, lower frailty, and enhanced QOL.
Keywords: HIV; Anemia; Anemia type; Macrocytosis; Microcytosis; Anemia of chronic disease; Ferritin; Clinical outcomes; Quality of life; Antiretroviral therapy